Forward trading and collusion of firms in volatile markets - Markus F. Aichele (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Assuming deterministic demand Liski and Montero (2006) show that forward trading is able to facilitate collusion. We present a more concise model incorporating the main reason for forward trading: Uncertainty. In general, fl uctuations make collusion harder to sustain (Rotemberg and Saloner, 1986). However, using forward contracts, firms are able to decrease the incentives to deviate from a collusive agreement even in very volatile markets. This makes collusive strategies more sustainable and decreases social welfare.
Keywords: L40; D43; K21; 330